Biocontrol of Late Blight Disease (Phytophthora capsici) of Pepper and the Plant Growth Promotion by Paenibacillus ehimensis KWN38. Issue 6 (15th November 2013) - Naing, Kyaw W.; Anees, Muhammad; Nguyen, Xuan H.; Lee, Yong S.; Jeon, Seung W.; Kim, Sang J.; Kim, Myung H.; Kim, Kil Y.
Abstract For field application of a bacterial strain used to control Phythophthora capsici, we will need a biologically and economically efficient carrier medium. The known antagonist Paenibacillus ehimensisKWN38 was grown in a grass medium where it showed high antifungal and lytic enzyme activities. To demonstrate the potential of P. ehimensisKWN38 for biocontrol of late blight disease in pepper, pot trials were conducted by treating the 1‐month‐old plants with water (W), a selected grass medium (G3), G plus P. ehimensisKWN38 inoculation (G3P) or synthetic fungicide (F). The shoot dry weight in G3P was higher than that in W and F treatments at 15 days after zoospore infection (DZI). The root dry weight in G3P was also higher than that in W. The root mortality of G3 and W increased over 58 and 80% at 15 DZI, and some plants in those treatments wilted due to the failure of root physiology. The plants in G3P and F survived well because of their better root health conditions. Soil cellulase activity of G3P was consistently higher than that of W and F at earlier observation times (0, 2 and 6 DZI). The root β‐1, 3‐glucanase activity of G3P promptly increased to maximum shortly after zoospore infection and reached the maximum value of 51.12 unit g−1 of fresh weight at 2 DZI. All these results indicate that inoculation of P. ehimensisKWN38 to the root zone of potted pepper plants increases plant growth, root and soil enzyme activities and alleviates the root death caused by infection with P. capsici zoospores.